2016
DOI: 10.3748/wjg.v22.i21.4999
|View full text |Cite
|
Sign up to set email alerts
|

Phosalone-induced inflammation and oxidative stress in the colon: evaluation and treatment

Abstract: This research highlights that EA is effective to alleviate the side effects of phosalone by reducing the level of oxidative stress and inflammatory proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…In contrast, NF-κB was a potential target for the anti-inflammatory effect of ellagic acid incorporated into the normal diet (0.5 %) of mice in an ulcerative colitis experimental model [97]. Similar results for ellagic acid as an anti-inflammatory agent through modulation of the NF-κB activation pathway have been observed in several other studies [98][99][100][101][102].…”
Section: Anti-inflammatory Activity Of Ellagic Acidsupporting
confidence: 76%
“…In contrast, NF-κB was a potential target for the anti-inflammatory effect of ellagic acid incorporated into the normal diet (0.5 %) of mice in an ulcerative colitis experimental model [97]. Similar results for ellagic acid as an anti-inflammatory agent through modulation of the NF-κB activation pathway have been observed in several other studies [98][99][100][101][102].…”
Section: Anti-inflammatory Activity Of Ellagic Acidsupporting
confidence: 76%
“…(2013), who suggested that EA reduced NF-B, IL-6, and TNF levels compared to the control group in mice with ulcerative colitis [ 36 ]. EA inhibits inflammation through modulating the NF-B signaling pathway [ 37 ]. These findings are consistent with Cornélio Favarin et al .…”
Section: Discussionmentioning
confidence: 99%
“…Several pesticides exert cellular toxicity via the triggering of oxidative stress, such as organophosphorus insecticides (35), organochlorine insecticides (36), pyrethroid insecticides (37), and fungicides (38), but the mechanisms by which FEN induces oxidative hepatic damage are still poorly understood. Therefore, we first profiled hepatic gene expression in FEN-exposed rats.…”
Section: Discussionmentioning
confidence: 99%